2012
DOI: 10.1039/c2np00088a
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide: structural modifications, structure–activity relationships, bioactivities, clinical development and mechanisms

Abstract: Triptolide, a principal bioactive ingredient of Tripterygium wilfordii Hook F, has attracted extensive exploration due to its unique structure of a diterpenoid triepoxide and multiple biological activities. This review will focus on the structural modifications, structure-activity relationships, pharmacology, and clinical development of triptolide in the last forty years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
207
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(217 citation statements)
references
References 126 publications
(181 reference statements)
2
207
0
8
Order By: Relevance
“…28 In addition, TPL was proved efficient in reducing tumor growth and prolonging the living time. [29][30][31] TPL can also enhance the activities of chemotherapeutic agents in colon carcinoma cells, myeloma cell lines, and human oral cavity squamous cell carcinoma cells. [32][33][34] As reported, the combination of TPL with other anticancer drugs resulted in synergistic effects and promoted apoptosis but did not intensify the side effects of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…28 In addition, TPL was proved efficient in reducing tumor growth and prolonging the living time. [29][30][31] TPL can also enhance the activities of chemotherapeutic agents in colon carcinoma cells, myeloma cell lines, and human oral cavity squamous cell carcinoma cells. [32][33][34] As reported, the combination of TPL with other anticancer drugs resulted in synergistic effects and promoted apoptosis but did not intensify the side effects of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that of the 17 identified antiangiogenic compounds, 4 compounds, namely, pseudolaric acid B, MFTZ-1, 10-hydroxycamptothecin and triptolide, can indirectly inhibit the VEGF-VEGFR axis by decreasing cellular HIF-1α accumulation and thereby reducing VEGF expression and secretion [15][16][17][18][19][20][21] (Figure 1). We define these compounds to be HIF-1α-VEGF axis inhibitors.…”
Section: Hif-1α-vegf Axis Inhibitorsmentioning
confidence: 97%
“…In contrast to the previous 3 inhibitors, triptolide may enhance the levels of cellular HIF-1α mRNA and protein [20] . However, triptolide also causes the downregulation of VEGF expression and secretion [20] , possibly because it binds to XPB (which is also known as ERCC3) and causes the degradation of RNA polymerase II [21] , disrupting the transcriptional function of HIF-1α.…”
Section: Hif-1α-vegf Axis Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triptolide is effective against a number of malignancies, including ovarian cancer, breast cancer, pancreatic cancer and neuroblastoma (6). Triptolide supresses the proliferation of prostate cancer cells by inhibition of expression of SUMO-specific protease 1 (7).…”
Section: Introductionmentioning
confidence: 99%